Literature Review : Analisis Faktor yang Berhubungan dengan Tingkat Konsumsi Minuman Berpemanis pada Remaja - Santi Puspitasari; Marthia Ikhlasiah (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
High consumption of sugar-sweetened beverages (SSBs) has become an increasing public health concern, particularly among adolescents. Excessive SSB intake is a major risk factor for various non-communicable diseases, including type 2 diabetes mellitus, cardiovascular diseases, obesity, dental caries, and certain types of cancer. This study aimed to analyze the factors associated with the level of sugar-sweetened beverage (SSB) consumption among adolescents. This study employed a descriptive literature review approach. Data were obtained from national and international journals relevant to the topic of SSB consumption among adolescents. The selected articles were analyzed to identify factors associated with SSB consumption. The findings indicated that SSB consumption among adolescents is influenced by several factors, including individual factors (gender and knowledge), socioeconomic factors (peer influence and pocket money allowance), environmental factors (mass media exposure and beverage availability), and psychological factors (stress level and preference for sweet tastes). This study highlights that SSB consumption is a multifactorial behavior influenced by various interacting determinants. Therefore, comprehensive interventions targeting both individual and environmental factors are needed to reduce SSB consumption among adolescents.